Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,369 questions

17,804 answers

1,438 comments

36,292 users

Substitution with Two Variables

0 votes

equation

asked Dec 31, 2017 in ALGEBRA 1 by anonymous

1 Answer

0 votes

The equations are

6y + x   =   1  ------------------------------------>  (1)

4x + 18   =   9y  ----------------------------------------->  (2)

From equation (1)

x  =  1 - 6y

Substitute x  =  1 - 6y in equation (2)

4(1 - 6y) + 18   =   9y

4 - 24y + 18   =   9y

22   =   9y + 24y

22   =   33y

y   =   22/33

y   =   2/3

Substitute y = 2/3 in equation (1)

6(2/3) + x   =   1

2(2) + x   =   1

4 + x   =   1

x   =   1 - 4

x   =   -  3

The solution is x = -3 and y = 2/3.

answered Dec 31, 2017 by homeworkhelp Mentor

Related questions

...